NILL Concept Store Online System - Ibrahim, Yasin; Mohamed, Rozlini (Applied Information Technology And Computer Science, 2026)
NILL Concept Store Online System addresses the limitations of face-to-face traditional clothing sales by launching a comprehensive e-commerce platform. Developed to overcome seasonal dependence and expand market reach, the system enhances customer experience and streamlines administration. Key features include user registration and login, product management, shopping cart, sales tracking, delivery monitoring, reporting, and color suggestion tools. Built with standard web technologies (VS Code, PhpMyAdmin) and tested on Chrome and Edge, it meets performance, security, and compatibility requirements. The platform significantly improves product accessibility, automates orders and payments, and provides real-time inventory updates. Sales reporting enables effective trend analysis. This robust solution offers NILL a seamless, efficient online sales channel. Future enhancements could focus on advanced personalization and marketing integration to further boost engagement and performance.